Phylogenetic Diversity and Symbiotic Effectiveness of Bradyrhizobium Strains Nodulating Glycine max in Côte d’Ivoire - Marie Ange Akaffou; Romain Kouakou Fossou; Anicet Ediman Théodore Ebou; Zaka Ghislaine Claude Kouadjo-Zézé; Chiguié Estelle Raïssa-Emma Amon; Clémence Chaintreuil; Saliou Fall; Adolphe Zézé (Agronomy)
Soybean (Glycine max) is a protein-rich legume crop that plays an important role in achieving food security. The aim of this study was to isolate soybean-nodulating rhizobia from Côte d’Ivoire soils and evaluate their potential as efficient strains in order to develop local bioinoculants. For this objective, 38 composite soil samples were collected from Côte d’Ivoire’s five major climatic zones. These soils were used as substrate to trap the nodulating rhizobia using the promiscuous soybean variety R2-231. A total of 110 bacterial strains were isolated and subsequently identified. The analysis of ITS (rDNA16S-23S), glnII and recA sequences revealed a relatively low genetic diversity of these native rhizobia. Moreover, the ITS phylogeny showed that these were scattered into two Bradyrhizobium clades dominated by the B. elkanii supergroup, with ca. 75% of all isolates. Concatenated glnII-recA sequence phylogeny confirmed that the isolates belong in the majority to ‘B. brasilense’, together with B. vignae and some putative genospecies of Bradyrhizobium that needs further elucidation. The core gene phylogeny was found to be incongruent with nodC and nifH phylogenies, probably due to lateral gene transfer influence on the symbiotic genes. The diversity and composition of the Bradyrhizobium species varied significantly among different sampling sites, and the key explanatory variables identified were carbon (C), magnesium (Mg), nitrogen (N), pH, and annual precipitation. Based on both shoot biomass and leaf relative chlorophyll content, three isolates consistently showed a higher symbiotic effectiveness than the exotic inoculant strain Bradyrhizobium IRAT-FA3, demonstrating their potential to serve as indigenous elite strains as bioinoculants.